Design Methodology for Reducing RIN Level in DFB Lasers - Hisham, Hisham K. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
The relative intensity noise (RIN) characteristics in distributed feedback (DFB) lasers are analyzed theoretically by proposing a new methodology. In addition to temperature variation (T), the effect of other model parameters such as injection current (I inj ), active layer volume (V), spontaneous emission (β sp ) and gain compression (ε) factors on RIN characteristics is investigated. The numerical simulations shows, the peak RIN level can be reduced to around –150 dB/Hz, while relaxation oscillation frequency (ROF) is shifted towards 5.6 GHz. In addition, the RIN level is increased with temperature by the rate of 0.2 dB/ºC and ROF is reduced by the rate of 0.018 GHz/ºC. Results show, the low RIN level can be obtained by selecting model parameters reasonably.